1998
DOI: 10.1109/2944.686755
|View full text |Cite
|
Sign up to set email alerts
|

Temporal contrast in Ti:sapphire lasers, characterization and control

Abstract: Abstract-As ultrafast lasers achieve ever higher focused intensities on target, the problem of ensuring a clean laser-solid interaction becomes more pressing. In this paper, we give concrete examples of the deleterious effects of low-contrast interactions, and address the problem of subpicosecond laser intensity contrast ratio on both characterization and control fronts. We present the new technique of high-dynamic-range plasma-shuttered streak camera contrast measurement, as well as two efficient and relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Some techniques for improving temporal contrast, such as femtosecond preamplification 2 and the use of a saturable absorber 2,3 have been proposed. Also, it has been demonstrated that an efficient way to clean the pulse after preamplification is to set up a nonlin-ear filter, as was first illustrated by a nonlinear elliptical polarization rotation 4,5 (NER) in hollow waveguides filled with xenon, with a limited input energy of 100 J.…”
mentioning
confidence: 99%
“…Some techniques for improving temporal contrast, such as femtosecond preamplification 2 and the use of a saturable absorber 2,3 have been proposed. Also, it has been demonstrated that an efficient way to clean the pulse after preamplification is to set up a nonlin-ear filter, as was first illustrated by a nonlinear elliptical polarization rotation 4,5 (NER) in hollow waveguides filled with xenon, with a limited input energy of 100 J.…”
mentioning
confidence: 99%
“…Saturable absorber has been proposed and demonstrated [31,40,[62][63][64][65][66][67] to be an effective means to improve the temporal contrast with a rise time much faster than Pockels cells. To take advantage of this method, the laser pulse must have a fast rise time; therefore, it is best to employ saturable absorber before the pulse stretcher.…”
Section: Temporal Specifications Of the 110-tw And The 13-tw Beamlinesmentioning
confidence: 99%
“…This pulse pedestal includes low intensity background energy over a nanosecond time scale from a number of sources within the CPA femtosecond laser system including amplified spontaneous emission (ASE), pre and post pulses, spectral wings from grating mismatch, and other sources described in the literature. Furthermore it has been shown that the presence of this pedestal can influence ultrashort experimentation [7][8][9][10] and merits additional study [11,12]. Efforts to reduce the pedestal have been shown to improve the quality of the beam and experimental results [13].…”
Section: Introductionmentioning
confidence: 96%